2017
DOI: 10.1145/3130899
|View full text |Cite
|
Sign up to set email alerts
|

Drone Near Me

Abstract: Personal drones are becoming more mainstream and are used for a variety of tasks, such as delivery and photography. The exposed blades in conventional drones raise serious safety concerns. To address this, commercial drones have been moving towards a safe-to-touch design or have increased safety by adding propeller guards. The affordances of safe-to-touch drones enable new types of touch-based human-drone interaction. Various applications have been explored, such as augmented sports and haptic feedback in virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 11 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Regarding RQ 1 , we found that the most frequently implemented system functions for drone video cameras have been taking photos [7,8,13,33,36] and selfies [1,[8][9][10]13,30,36], while commands for recording videos have been addressed to a less extent [7,36]. We identified six types of system functions relevant to our scope: (1) take selfie, (2) take picture, (3) take picture of a specified object, (4,5) start/stop video recording, and (6) stream video from the drone.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding RQ 1 , we found that the most frequently implemented system functions for drone video cameras have been taking photos [7,8,13,33,36] and selfies [1,[8][9][10]13,30,36], while commands for recording videos have been addressed to a less extent [7,36]. We identified six types of system functions relevant to our scope: (1) take selfie, (2) take picture, (3) take picture of a specified object, (4,5) start/stop video recording, and (6) stream video from the drone.…”
Section: Resultsmentioning
confidence: 99%
“…After screening the 77 references according to these eligibility criteria, we identified 10 papers that discussed, among others, controlling of the drone video camera [1,[7][8][9][10][11]13,30,33,36]. It is noteworthy that, except Chen et al's [11] work on view manipulation for drone photography and Chen et al's [10] direct pointing interaction technique for selfie drones, 5 none of the other works identified by our query had photography and/or video as their main scope of investigation for human-drone interaction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interacting with flying robots (aka drones) presents specific differences to interacting with ground robots. In particular, touch can be dangerous (although not impossible [1,17]), and audio feedback is compromised because of the noise [10]. We find several proposed interaction strategies in the literature.…”
Section: Human-drone Interactionmentioning
confidence: 99%